Tackling Gynecologic Cancer Disparities: An Assessment of 2 Interventions for Improving Information Exchange With Racial/Ethnic Communities. Issue 1 (2nd March 2023) - Adebayo, Nihmotallahi; Dunne, Will; Dean, Julie Robin; O'Brian, Catherine; Dahdouh, Rabih; Simon, Melissa A.
Abstract : Racial health disparities continue to greatly impact the incidence and mortality rates of gynecologic cancers. Although there are many drivers for these disparities, limited inclusion of vulnerable populations in clinical research and narrowed medical knowledge of patients are large contributors that disproportionately affect racial/ethnic communities. To mitigate these disparities, we must look for avenues that connect patients from these communities to cancer researchers. In this review, we summarize 2 projects that can serve as models for future interventions that promote education and engagement in clinical research for populations most impacted by gynecologic cancer disparities.